Financial sustainability of rural microfinance institutions (MFIs) in Tanzania - Nyamsogoro, G. Daniel (University of Greenwich (London), 2024)
A thesis Submitted in Partial fulfilment of the requirement of the university of Greenwich for the degree of Doctor of Philosophy - 2010